The Benefits and Burdens of Engaging in Argumentation: Trans*feminist Reflections on Tuvel’s “In Defense of Transracialism” - Kapusta, Stephanie (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
After considering some ways of assessing argumentation, I present an ethical assessment of Tuvel's argument in her article “In Defense of Transracialism.” My claim is that some transgender women engaging with Tuvel are exposed to certain kinds of injustice associated with argumentational work, namely, disproportionate burdens and risk of psychological harm.